2008
DOI: 10.1309/lwdy1axhxuulnvhq
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Melting Analysis for Rapid Detection ofKRAS, BRAF,andPIK3CAGene Mutations in Colorectal Cancer

Abstract: High-resolution melting analysis (HRMA) provides a valid approach to efficiently detect DNA genetic and somatic mutations. In this study, HRMA was used for the screening of 116 colorectal cancers (CRCs) to detect hot-spot mutations in the KRAS and BRAF oncogenes. Mutational hot spots on the PIK3CA gene, exons 9 and 20, were also screened. Direct sequencing was used to confirm and characterize HRMA results. HRMA revealed abnormal melting profiles in 65 CRCs (56.0%), 16 of them harboring mutations in 2 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
119
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 40 publications
(51 reference statements)
16
119
0
10
Order By: Relevance
“…Using a pre-screening approach in codons 12 -13 with high-resolution melting curve analysis (Simi et al, 2008) followed by sequencing, we found 35% cases with a mutation in codons 12 -13, in agreement with the literature. However, we also report two cases presenting a mutation in codon 19 (c.57G4C, p.Leu19Phe), without mutations in codons 12 -13.…”
Section: Sirsupporting
confidence: 90%
“…Using a pre-screening approach in codons 12 -13 with high-resolution melting curve analysis (Simi et al, 2008) followed by sequencing, we found 35% cases with a mutation in codons 12 -13, in agreement with the literature. However, we also report two cases presenting a mutation in codon 19 (c.57G4C, p.Leu19Phe), without mutations in codons 12 -13.…”
Section: Sirsupporting
confidence: 90%
“…In a previous study 29 on colorectal cancer, we demonstrated the high sensitivity of HRM analysis, which allowed identifying at least 5% of mutated alleles in a background of wild-type DNA. Even though HRM analysis has been widely applied for the screening of somatic variants in biopsies of solid cancers, only a few previous applications of HRM analysis have been reported in the screening of cytological material, as fixed fresh cells 36 or scraped cells from archival slides 37 obtained from needle aspiration.…”
Section: Discussionmentioning
confidence: 98%
“…Screening the FNAB samples provided a satisfactory resolution of melting for all of the DNA sites of interest and allowed the amplification of all genes simultaneously. To evaluate the theoretical sensitivity of our method, a detection limit was calculated, as described previously, 29 by using serial dilution of positive controls (cell lines CCRF-CEM, SW948, HT1197, SK-MEL28) in wild-type DNA (from MCF-7 cell line) for each gene under study. We were able to detect the presence of mutated DNA up to 5% in a background of wild-type DNA (data not shown).…”
Section: Mutation Scanning By Hrm Analysis and Sequencingmentioning
confidence: 99%
“…High-resolution melting has been used clinically to detect somatic changes in select exons of oncogenes such as EGFR, 53 KRAS, 54 PDGFRA, 55 KIT, 56 BRAF, 57 and TP53. 58 In tumors with mixed populations of tumor and normal cells, the sensitivity of scanning (Ͻ10%) is superior to sequencing (ϳ20%).…”
Section: Mutation Scanning By Meltingmentioning
confidence: 99%